Coding of Coefficients of two-dimensional non-separable Adaptive Wiener Interpolation Filter - Vatis, Yuri; Edler, Bernd; Wassermann, Ingolf; Nguyen, Dieu Thanh; Ostermann, Jörn (Visual Communications and Image Processing 2005, 2005)
Standard video compression techniques apply motion-compensated prediction combined with transform coding of the prediction error. In the context of prediction with fractional-pel motion vector resolution it was shown, that aliasing components contained in an image signal are limiting the prediction accuracy obtained by motion compensation. In order to consider aliasing, quantisation and motion estimation errors, camera noise, etc., we analytically developed a two-dimensional (2D) non-separable interpolation filter, which is calculated for each frame independently by minimising the prediction error energy. For every fractional-pel position to be interpolated, an individual set of 2D filter coefficients is determined. Since transmitting filter coefficients as side information results in an additional bit rate, which is almost independent for different total bit rates and image resolutions, the overall gain decreases when total bit rates decrease. In this paper we present an algorithm, which regards the non-separable two-dimensional filter as a polyphase filter. For each frame, predicting the interpolation filter impulse response through evaluation of the polyphase filter, we only have to encode the filter coefficients prediction error. This enables bit rate savings, needed for transmitting filter coefficients of up to 75% compared to PCM coding. A coding gain of up to 1,2 dB Y-PSNR at same bit rate or up to 30% reduction of bit rate is obtained for HDTV-sequences compared to the standard H.264/AVC. Up to 0,5 dB (up to 10% bit rate reduction) are achieved for CIF-sequences.
UnivIS-Import:2015-04-20:Pub.2005.tech.IE.aulab.zentr.coding
Keywords: Adaptive interpolation; Adaptive Wiener filter; H.264/AVC; Video coding